Estructura y dinámica de comunidades asociadas a cultivos de Gracilariopsis tenuifrons (Gracilariaceae) en Chacopata, Sucre, Venezuela. I: Inventario faunístico - Barrios, Jorge; Lemus, Andrés (Revista de Biología Tropical, 2000)
The associated fauna of Gracilariopsis tenuifrons (Gracilariaceae, Rhodophyta) cultures was collected between October 1994 and December 1996 in Chaeopata (Sucre State, Venezuela) and preserved in 10% formaldehyde. The species list includes 17 Crustacea, 14 Mollusca and six Polychaeta, the remaining taxa added ten species (total 47 species in eight Phyla). Grazing by mesoherbivores affected the algae and the mollusk Aplysia protea damaged new cultures significantly. The abundance of tubes built by the amphipod Eurirthonius brasiliensis impairs algal aspect and facilitates colonization by other organisms.